Sanitation and water supply coverage thresholds associated with active trachoma: Modeling cross-sectional data from 13 countries. - Joshua V Garn; Sophie Boisson; Rebecca Willis; Ana Bakhtiari; Tawfik Al-Khatib; Khaled Amer; Wilfrid Batcho; Paul Courtright; Michael Dejene; Andre Goepogui; Khumbo Kalua; Biruck Kebede; et al. (Public Library of Science (PLoS), 2018)
Facial cleanliness and sanitation are postulated to reduce trachoma transmission, but there are no previous data on community-level herd protection thresholds. We characterize associations between active trachoma, access to improved sanitation facilities, and access to improved water sources for the purpose of face washing, with the aim of estimating community-level or herd protection thresholds.We used cluster-sampled Global Trachoma Mapping Project data on 884,850 children aged 1-9 years from 354,990 households in 13 countries. We employed multivariable mixed-effects modified Poisson regression models to assess the relationships between water and sanitation coverage and trachomatous inflammation-follicular (TF). We observed lower TF prevalence among those with household-level access to improved sanitation (prevalence ratio, PR = 0.87; 95%CI: 0.83-0.91), and household-level access to an improved washing water source in the residence/yard (PR = 0.81; 95%CI: 0.75-0.88). Controlling for household-level water and latrine access, we found evidence of community-level protection against TF for children living in communities with high sanitation coverage (PR80-90% = 0.87; 95%CI: 0.73-1.02; PR90-100% = 0.76; 95%CI: 0.67-0.85). Community sanitation coverage levels greater than 80% were associated with herd protection against TF (PR = 0.77; 95%CI: 0.62-0.97)-that is, lower TF in individuals whose households lacked individual sanitation but who lived in communities with high sanitation coverage. For community-level water coverage, there was no apparent threshold, although we observed lower TF among several of the higher deciles of community-level water coverage.Our study provides insights into the community water and sanitation coverage levels that might be required to best control trachoma. Our results suggest access to adequate water and sanitation can be important components in working towards the 2020 target of eliminating trachoma as a public health problem.